1998
DOI: 10.1002/stem.160208
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of Peripheral Blood Progenitor Cells by Betafectin® PGG‐Glucan Alone and in Combination with Granulocyte Colony‐Stimulating Factor

Abstract: Betafectin® PGG-Glucan, a novel β-(1,6) branched β-(1,3) glucan purified from the cell walls of Saccharomyces cerevisiae, has been shown to synergize with myeloid growth factors in vitro and to enhance hematopoietic recovery in myelosuppressed mice and primates. Here we report that PGG-Glucan is also capable of mobilizing peripheral blood progenitor cells (PBPC). PGG-Glucan (0.5 mg/kg to 16 mg/kg) was administered intravenously to C3H/HeN male mice and blood collected at times ranging from 30 min to seven days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 37 publications
3
29
0
1
Order By: Relevance
“…Recent studies have shown that after hematopoietic injury or G-CSF mobilization, stroma cells express iC3b and tether CR3 ϩ hematopoietic progenitor cells, suggesting that betaglucan may be able to enhance their proliferation (9). PGG (poly-␤1-6-glucotriosyl-␤1-3-glucopyranose)-glucan has been shown to enhance the effect of G-CSF on hematopoiesis in C3H/HeN mouse cells (27) and in human bone marrow cells (38). However, PGG-glucan does not induce G-CSF production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that after hematopoietic injury or G-CSF mobilization, stroma cells express iC3b and tether CR3 ϩ hematopoietic progenitor cells, suggesting that betaglucan may be able to enhance their proliferation (9). PGG (poly-␤1-6-glucotriosyl-␤1-3-glucopyranose)-glucan has been shown to enhance the effect of G-CSF on hematopoiesis in C3H/HeN mouse cells (27) and in human bone marrow cells (38). However, PGG-glucan does not induce G-CSF production.…”
Section: Discussionmentioning
confidence: 99%
“…However, dose-response relationships have not been shown (15,21). Since other beta-glucans have been found to reduce myelosuppression and to enhance hematopoiesis in vitro and the mobilization of stem cells in vivo in animal models (16,27,33), we initially tested the effects of MBG on mouse bone marrow cells. Those studies showed for the first time that MBG enhances murine bone marrow cell proliferation and differentiation into granulocytesmacrophages (GMs) in a dose-dependent manner (22).…”
mentioning
confidence: 99%
“…These facts suggest that SCG induces hematopoietic response in normal mice. Patchen et al 46) reported that the administration of a yeast b-glucan preparation, PGG-glucan, enhanced the production of peripheral blood progenitor cells (PBPC) in mice. It is also well documented that B cells are more susceptible to CY-treatment than T cells.…”
Section: Cd8mentioning
confidence: 99%
“…In contrast to most other ␤-glucan preparations, PGG-glucan does not directly stimulate leukocyte microbicidal functions in vitro, but rather primes or enhances their responsiveness to bacteria and other stimuli [3,29]. PGG-glucan also does not directly stimulate or enhance the production of pro-inflammatory cytokines either in vitro or in vivo [3,24,29,30,31].…”
Section: Introductionmentioning
confidence: 99%